Comparative evaluation of cytotoxic and anti-metastatic function of microbial chondroitin sulfate and animal-originated commercial chondroitin sulfate in cancer cells : Effects of microbial CS and commercial CS in cancer cells - Unver, Tuba; Celik-Uzuner, Selcen; Erenler, Ayse Sebnem (Cellular and Molecular Biology, 2023)
Cancer has the second-highest mortality rate worldwide after cardiovascular disease. In addition, breast and cervical cancer are two of the leading causes of cancer-related deaths among women. The tumor microenvironment, which consists of fibroblasts, immune cells, cells that form blood vessels, and proteins, is a therapeutic target for cancer therapy. As part of the cellular microenvironment, glycosaminoglycan chondroitin sulfate is associated with various aspects of tumor progression and metastasis depending on the sulfate pattern of chondroitin sulfate. This study evaluated the roles of Microbial Chondroitin Sulfate (CS) and Commercial CS in tumor growth and metastasis comparatively using MDA-MB-231 metastatic breast cancer cells, HeLa cervical cancer cells, and normal fibroblasts. In addition, the role of CS types in wound healing was also assessed comparatively. Microbial CS was more cytotoxic in MDA-MB-231 cells than HeLa compared to Commercial CS. Although both CS reduced cell viability in normal cells, the selective index of Microbial CS in MDA-MB-213 cells was higher than its commercial counterpart. In addition, the role of CS types in wound healing was also assessed comparatively. Both types of CS decreased the cell migration in MDA-MB-231 cancer cells, but HeLa cells were more sensitive to Microbial CS than Commercial CS to heal the wound. The wound healing of NIH3T3 cells after Microbial CS was similarly high to the healing after Commercial CS. This preliminary study shows that microbial CS produced by biotechnological methods from a recombinant source created by our team can be an effective therapeutic agent in various types of cancer.